2020
DOI: 10.1017/inp.2020.7
|View full text |Cite
|
Sign up to set email alerts
|

Hot water and cutting for control ofImpatiens glandulifera

Abstract: Ornamental jewelweed (Impatiens glandulifera Royle) is an alien invasive plant in Europe. This annual plant often grows in riparian habitats where herbicides are prohibited. Several studies have reported the negative effect on ecosystem and ecosystem services by this species. However, limited research is published on control measures and the aim of our study was to explore use of hot water and cutting to control I. glandulifera. A lab experiment showed that the lethal water temperature for seed was between 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…While hot water application can control weeds, it has been reported that at much lower doses the seeds of Impatiens glandulifera, a problem in European countries, lose their ability to germinate. When comparing the effects of mowing and hot water in controlling Impatiens glandulifera, they reported that applying hot water at different stages of plant growth was more effective than mowing and that applying hot water in the early and late stages could save 50% of the water used (Oliver et al, 2020). The results of this study parallel the results obtained in our study.…”
Section: Discussionsupporting
confidence: 85%
“…While hot water application can control weeds, it has been reported that at much lower doses the seeds of Impatiens glandulifera, a problem in European countries, lose their ability to germinate. When comparing the effects of mowing and hot water in controlling Impatiens glandulifera, they reported that applying hot water at different stages of plant growth was more effective than mowing and that applying hot water in the early and late stages could save 50% of the water used (Oliver et al, 2020). The results of this study parallel the results obtained in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Can$21,000 ha -1 in Québec, Canada) (Leblanc and Lavoie, 2017). Spraying hot water of 80°C on the plants has also been tested as a management strategy, but cutting is more time and cost efficient (Oliver et al, 2020).…”
Section: Mechanical Controlmentioning
confidence: 99%
“…Thus, habitat restoration is a must, along with removal [ 58 ]. Chemical control is an available [ 75 ] but a not yet viable choice for riparian habitats [ 183 ]. Mechanical control is expensive and laborious [ 184 ].…”
Section: Discussionmentioning
confidence: 99%